Global riverine theoretical hydrokinetic resource assessment. (August 2021) - Ridgill, Michael; Neill, Simon P.; Lewis, Matt J.; Robins, Peter E.; Patil, Sopan D.
Abstract: Hydrokinetic energy conversion refers to the conversion of kinetic energy in moving water to electricity. It offers an alternative to conventional hydropower, with benefits of modularity and scalability, in addition to being environmentally and socially less impactful. This study aims to determine the theoretical global riverine hydrokinetic resource. We use a 35 year modelled daily discharge data set and vectorised representation of rivers, with near-global coverage and suitable spatiotemporal resolution, to determine the mean annual energy yield of 2.94 million river reaches. The mean global resource (excluding Greenland) is estimated to be 58 400 ± 109 TWh yr −1 (6.660 ± 0.012 TW). Consideration of global spatial distribution, by river reach, illustrates regional variation and shows a tendency for potential to be concentrated along major rivers and in areas of significant elevation change. China, Russia and Brazil are found to be the countries with the greatest potential. After normalisation by total river length, Bhutan, Nepal and Tajikistan also show great potential. Hydrokinetic energy conversion can benefit isolated communities currently without access to electricity. We consider how the specific advantages of this particular technology have the potential to be combined with and complement other established forms of renewable energy technology, providing the means to support the reduction of energy poverty. Highlights: Method developed for global riverine hydrokinetic resource assessment. Theoretical global riverine hydrokinetic resource estimated to be 58000 TWh/yr. Mean power of global rivers over the period 1979–2013 estimated to be 6.7 TW. China, Russia, Brazil, Bhutan, Nepal and Tajikistan offer great potential. Hydrokinetic energy conversion can benefit isolated communities in energy poverty.